Antibacterial Activity of Locally Prepared Herbal Cough Extracts against Klebsiella pneumoniae and Streptococcus pneumoniae - Atuheirwe, Maxine; Iramiot, Jacob Stanley (International Journal of Biochemistry Research & Review, 2019)
Cough due to Klebsiella pneumoniae and Streptococcus pneumoniae is currently managed by conventional antibiotics and herbal extracts in Uganda. However, much as these herbal extracts are extensively used, their antibacterial activity is not known. This study aimed at determining the antibacterial activity of the selected locally prepared herbal cough extracts against two bacterial strains i.e. Klebsiella pneumoniae (ATCC 700603), and Streptococcus pneumoniae (ATCC 49619). Methods: The herbal cough extracts were screened for antibacterial activity using Agar-well diffusion method for determining zone of inhibition, macro broth dilution method for Minimum Inhibitory Concentration (MIC) determination and Streak plate method for Minimum Bactericidal Concentration (MBC). Results: In vitro evaluation of antibacterial activity of the 5 brands of herbal cough extracts against K. pneumoniae and S. pneumoniae revealed that all extracts possessed significant antimicrobial effects against all microorganisms tested (p < 0.05). However, MM04 (35.6±0.0) mm and MM03 (33.6±1.5) mm had maximum zones of inhibition as compared to other herbal extracts against K. pneumoniae and S. pneumoniae respectively. Average MIC results for extracts against K. pneumoniae indicated that MM01 had the highest MIC (2.5000 mg/ml) while MM03 had the least MIC (0.0625 mg/ml). Average MIC results for extracts against S. pneumoniae showed MM01 had the highest MIC (2.0000 mg/ml) while MM03 3 had the least MIC (0.0438 mg/ml). Average MBC results for extracts against K. pneumoniae indicated that MM01 had the highest MBC (4.000 mg/ml) while MM03 had the least MBC (0.030 mg/ml). Average MBC results for extracts against S. pneumoniae showed MM01 had the highest MBC (4.000 mg/ml) while MM03 had the least MBC (0.033 mg/ml). Conclusion: The results obtained in present study were revealed that locally prepared herbal extracts had significant antibacterial activity. Hence they can be used as promising alternatives of antibiotics used against Respiratory Tract Infections due to K. pneumoniae and S. pneumoniae.
Keywords: Antibacterial activity; Herbal cough extracts; Klebsiella pneumoniae; Streptococcus pneumonia; Minimum inhibitory concentration; Minimum bactericidal concentration